Rhegmatogenous retinal detachment after retinopathy of prematurity laser treatment - Robert C. Gunzenhauser; Yoon H. Lee; Irena Tsui (American Journal of Ophthalmology Case Reports, 2023)
Purpose: Rhegmatogenous retinal detachment (RRD) after retinopathy of prematurity (ROP) laser is rare but has been reported to occur at the border of heavy laser or in combination with tractional retinal detachment (TRD). We describe a rare case of a RRD that developed during treatment for ROP with both laser and intravitreal injections. Observations: The retinal detachment resolved with scleral buckling surgery with residual macular atrophy. Conclusions and Importance: This case highlights the importance of retinal imaging, careful funduscopic examination, and consideration of the risk of RRDs after intravitreal injections and laser in neonates with ROP.